THE IMPLEMENTATION OF SHARIA AUDIT PROCESS, IMPLICATION OF SHARIA REGULATORY AND HUMAN RESOURCE ASPECTS - Rizqiani, Dian; Yulianto, Agung (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - Audit in Islamic Finance Institute (IFI) is important factor to ensure sharia compliance. This study aims to analyze the factors influencing the process of sharia audit in the IFI.Method - The population of this research is all of the intern auditor board Sharia Business Unit in Bank Jateng as many as 22 auditors. Sampling technique in this research is census sampling. The method of data collection used is  questionnaire. The data analysis used  are regression square linear and percentage descriptive analysis. There are three variables in this research which are regulation aspect, sharia resource development, and sharia audit.Result - The square linear regression analysis used SPSS for Windows Version 20 obtained the equation. The conclusion of this research is regulation toward the influence to the sharia audit, but sharia resource aspect is not. regulation and sharia resourch development toward the influence to the sharia audit.Implication - The suggestions for the next reseacher is multiply the sample and refference of research and choose Sharia Supervisory Board (SSB) as the respondent for get the relevant result.Originality - This research empirically examines the factors that influence the implementation of sharia audits at the Central Java Islamic bank. The type of research used is quantitative, because from a number of references found, the topic of sharia auditing that is widely studied is the level of concept with qualitative research type.